AB0772 Prospective study of cardiovascular risk assessment in systemic sclerosis. (12th June 2018) - Gonzalez Martin, J.J.; Novella-Navarro, M.; Cabrera Alarcón, J.L.; Carrión, O.; Abdelkader, A.; Calvo, E.; Alcocer, P.; Aramburu, F.; Marin, C.; Sainz, F.; Peña, P. García de la.; ,
Abstract : Objectives: Evaluate evolution of cardiovascular risk (CVR) in a cohort of systemic sclerosis (SSc) in one year of follow-up. Methods: Prospective longitudinal study of a cohort of 45 patients with SSc during a period of one year. Sociodemographic and analytical variables were analysed at the time of inclusion in the study (baseline) and after 12 months of follow-up. The vascular protocol with carotid ultrasound was performed, including the determination of carotid intima-media thickness (IMT) and the evaluation of atheromatous plaques; in addition to the performance of the ankle-brachial index (ABI) and the determination of endothelial dysfunction (ED) through the measurement of flow-mediated vasodilation (FMVD), all at baseline and at one year. Results: 45 patients were included, 94% of them female, with a mean age of 52.2±11.5 years and mean evolution time of 4.6±5.1 years. The distribution by subgroups was 44.4% limited SSc, 35.5% diffuse SSc, 4.4% pre-scleroderma, 4.4% sine scleroderma SSc, 6.6% MTCD, and 4.4% overlap syndrome. Classical CVR variables were collected as smoking habit, DM, HTN, obesity, DLP, hyperhomocysteinemia, and clinical variables of the SSc were added such as modified Rodnan Skin Score (mRSS), pulmonary arterial hypertension (PAH), interstitial lung disease (ILD), capillaroscopic pattern, SSc specific antibodies and previous treatments. A bivariate analysis was performed using binomial logistic regression, both at baseline and at one year. Pathological IMT (>0.9 mm) was significantly associated with hyperhomocysteinemia (p=0.024, OR=3.03, CI 1.33–9.58). The presence of atheromatous plaque was associated with corticosteroid treatment (p=0.048, OR=0.58, CI 0.28–0.97). Pathological ITB (<0.9) was significantly associated with the 25-OH-vitamin D deficit (p=0.031, OR=0.25, CI 0.06–0.77). ED did not show a statistically significant association with the parameters studied. To evaluate the effect of time, a binomial model was adjusted by linear regression of mixed effects for the variables of CV affectation considered (see table 1). Time proved to be a risk factor to present pathological ITB values, since it was evidenced at baseline in 4.4% of the sample compared to 20% in the one-year study. Consequently, a multivariate analysis was performed showing pathological ABI was significantly associated to time (p<0.001, OR=59.7, CI 59.64–59.75) and mRSS, although with little effect (p<0.001, OR=0.042, IC 0.036–0.047). Time was not a risk factor for the appearance of pathological IMT, ED or plaques. Conclusions: In our study, we observed the significant variation in ABI in one year, this may be due to the fact that this measurement has a high sensitivity for the detection of early peripheral arterial disease, in those patients who have not manifested signs and symptoms of arterial disease due to more evolved time of evolution. Acknowledgements: Thank you Casandra Jimenez for her help with the vascular database compilation Disclosure of Interest: None declared